2021
DOI: 10.3390/antiox10111855
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of the Novel Barbiturate Derivative MHY2699 in an MPTP-Induced Mouse Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is one of the most common neurodegenerative disorders, and is caused by the death of dopamine neurons and neuroinflammation in the striatum and substantia nigra. Furthermore, the inflammatory response in PD is closely related to glial cell activation. This study examined the neuroprotective effects of the barbiturate derivative, MHY2699 [5-(4-hydroxy 3,5-dimethoxybenzyl)-2 thioxodihydropyrimidine-4,6(1H,5H)-dione] in a mouse model of PD. MHY2699 ameliorated MPP⁺-induced astrocyte activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that MPP + neurotoxin triggers glial activation and neuroinflammation by increasing levels of GFAP (glial fibrillary acidic protein) and proinflammatory cytokines in primary astrocytes [17][18][19]. We pre-treated primary astrocytes with 1 µM of IAGIP for 6 h and then co-treated them with 200 µM of MPP + for 24 h. Immunocytochemistry (ICC) and Western blotting showed that IAGIP suppressed MPP +induced GFAP increases in primary astrocytes (Figure 1A-C).…”
Section: Iagip Downregulated Astrocyte Activation and Inflammatory Re...mentioning
confidence: 81%
“…Previous studies have demonstrated that MPP + neurotoxin triggers glial activation and neuroinflammation by increasing levels of GFAP (glial fibrillary acidic protein) and proinflammatory cytokines in primary astrocytes [17][18][19]. We pre-treated primary astrocytes with 1 µM of IAGIP for 6 h and then co-treated them with 200 µM of MPP + for 24 h. Immunocytochemistry (ICC) and Western blotting showed that IAGIP suppressed MPP +induced GFAP increases in primary astrocytes (Figure 1A-C).…”
Section: Iagip Downregulated Astrocyte Activation and Inflammatory Re...mentioning
confidence: 81%